Performance Analysis of an Information Technology Support Team - Rini Sejati, Pri Budiarti; Rajab, Ridwan; Karunia, R. Luki (KnE Social Sciences, 2022)
This study aimed to describe the competence of members of the information and technology support team at The Document Processing Center in order to optimize the performance of the team. Performance was analyzed based on competencies consisting of education, skills and motivation. Qualitative research methods were used with a descriptive approach. Data collection was through interviews, observations, document review and triangulation. The results of the study showed that the competence of the team members was already good, even though there was no established formal education or training and most did not have an information technology educational background. They were enthusiastic to learn and gain knowledge or skills from the team leader and fellow members, while they also carried out self-learning for their tasks. Their high motivation was evident from the fast service, which was thanks to skills they had learned. Their motivation could be higher if they receive rewards. The team members should receive a transfer of knowledge from once or twice a month to four times a month. In addition, to be reliable in providing services and anticipating changes in the external environment, The Document Processing Center could be supported by implementing job shadowing, coaching, mentoring, apprenticeships, work rotations, and committee assignments. Rotation policies should be in accordance with the expertise of the staff, such as placing a member of the support team who has an educational background into the information technology team. Keywords: performance, competence, knowledge, skills, motivation